CCD readout of GEM-based neutron detectors - Fraga, F. A. F. (2002)
We report on the optical readout of the gas electron multiplier (GEM) operated with a gaseous mixture suitable for the detection of thermal neutrons: 3He-CF4. A CCD system operating in the 400-1000 nm band was used to collect the light. Spectroscopic data on the visible and NIR scintillation of He-CF4 are presented. Images of the tracks of the proton and triton recorded with a triple GEM detector are also shown.